On the question of transitive and intransitive verbs in Swahili - Schönhof-Wilkans, Agnieszka (Lingua Posnaniensis, 2012)
Swahili does not always make a clear distinction between transitive and intransitive verbs. The question seems to be complicated by the elaborate voice system of this agglutinative language. Subcategories of the Swahili verb such as stative, reciprocal, reflexive, causative, applicative and passive are marked by appropriate affixes. Swahili also applies infixes to signify objects within transitive verbs. Although modern Swahili dictionaries include information about verbal transitivity (TUK I 2001, 2004), it is far from complete. The purpose of this paper is to investigate the problem of transitive and intransitive verbs in Swahili taking into consideration some of the verbal categories, with particular emphasis on the relation of the category of voice to the category of transitivity. The current state of research on the category of transitivity in Swahili will be briefly presented. The material for the analysis has been obtained from various sources, such as Swahili grammars and dictionaries, Tanzanian newspapers and websites, as well as the author’s own field notes.